PENGARUH PENAMBAHAN IRON MILL-SCALE DAN TEMBAGA SEBAGAI MATERIAL PELAT BIPOLAR - Nisya Ulmiah; Fitri Suryani Arsyad; Deni Shidqi Khaerudini (Jurnal Teknosains, 2018)
Bipolar plate is an important component of proton exchange membrane fuel cell (PEMFC), which provides fuel and oxidant to reactive sites, collect produced current, and mechanical support for the cell in the stacks. This study concerns to find the optimum composition and sintering temperature of iron mills-cale in matrix aluminium as bipolar plate material. This work firstly carried out by downsizing aluminium flake from scrap into powder using high energy milling for 120 min and treated the iron mill-scale at 300 and 1000 oC for 60 min. The waste aluminium powder, after sieving of 150 mesh, was mixing with iron mill-scale containing 30 to 50 vol.% using shaker mill for 10 min. The mixed powders were then pressed 300 MPa and sintered with temperature of 500-600 oC for 60 min and flowed with N2 gas. The structural changes, physical, and mechanical properties of the sintered sample were studied by optical micrograph, density, porosity, hardness Vickers, and electrical conductivity test. The result showed that the optimum composition Fe is 40 vol. % and sinter temperature is 550 oC. Conductivity value of 45.406 S/cm and hardness 183.96 HV hasn’t meet expectation. Cu added containing 4-10 vol. % Fe aims to improve physical properties composites as bipolar plate material PEMFC. The result showed Cu 4 vol. % Fe can increase conductivity value 64.481 S/cm and hardness 340.13 HV.